Investigating Growth-Energy-Emissions Trilemma in South Asia - Adeleye, Bosede Ngozi; Akam, Darlington; Inuwa, Nasiru; Olarinde, Muftau; Okafor, Victoria; Ogunrinola, Ifeoluwa; Adekola, Paul (International Journal of Energy Economics and Policy, 2021)
Abstract This paper situates the 2030 United Nations Sustainable Development Goals (SDGs) 7, 8, and 13 to investigate the growth-energy-emissions trilemma. It uniquely contributes to the discourse by using carbon emissions per (emissions), GDP per capita (economic growth), energy use per capita (nonrenewable energy) and renewable energy from seven South Asian countries covering 1990 to 2019 to determine the effect of economic growth and energy use on emissions and if its interaction with either energy variant enhances or dims the effect of energy on emissions. Consistent findings from panel-corrected standard errors (PCSE), feasible generalized least squares (FGLS) and bootstrapping ordinary least squares (BOLS) reveal that: (1) economic growth intensifies emissions, (2) renewable energy exhibit emissions-reducing properties; (3) nonrenewable energy intensifies emissions, (4) economic growth sustains the emissions-reducing impact of renewable energy; and (5) economic growth diminishes the harmful effect of nonrenewable energy. Given these, we submit that the interaction of economic growth enables the "good" effect of renewable energy. At the same time, it reduces the "bad" effect nonrenewable energy on carbon emissions. These outcomes engender a new line of argument that the extent of economic growth cuts carbon emissions level. Therefore, economic growth is an essential determinant of carbon emissions. Policy implications discussed. Keywords: carbon emissions, economic growth, nonrenewable energy, renewable energy, South Asia JEL Classifications: C52, O40, O55, Q40, Q50 DOI: https://doi.org/10.32479/ijeep.11054